2018
DOI: 10.2174/2589645801812010019
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Sciatic Nerve Block in Below Knee Amputation Surgery: Sub Gluteal Versus Popliteal Approach

Abstract: Background:Ultrasound guided sciatic nerve block has been proved to be effective in pain control for lower limb surgeries, fortunately, it can be performed at different levels via different approaches. Aims:To compare the effectiveness of the sub-gluteal and the popliteal approaches of blocking the sciatic nerve as well as their success rate. Settings and Design:After approval of the ethical committee and obtaining a written informed consent from 56 ASA II, III patients aged 45-75 year, this prospective, rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Hussien et al . [ 4 ] in their study comparing the US-guided sciatic nerve block through popliteal and subgluteal approach found that the time taken to perform the block was 11 ± 4 minutes in the popliteal approach and 18.15 ± 4.7 minutes in the subgluteal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Hussien et al . [ 4 ] in their study comparing the US-guided sciatic nerve block through popliteal and subgluteal approach found that the time taken to perform the block was 11 ± 4 minutes in the popliteal approach and 18.15 ± 4.7 minutes in the subgluteal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound has the advantage of providing satisfactory intraoperative anesthesia results similar to prolonged postoperative analgesia that can last approximately 20 hours. 3 In this case reported, the patient required amputation of the limb above the knee due to of death of the lower limb in the right cruris region. Patients also require continuous anticoagulant treatment for high-risk thrombo-embolism and poor cardiovascular condition after the recent stroke.…”
Section: Introductionmentioning
confidence: 89%
“…Sciatic nerve block creates anesthesia to the skin on the back of the thigh, hamstrings, biceps, parts of the hip and knee joints, and the entire leg below the knee, except for the skin on the medial side of the bottom of the lower limb. 3,4 The femoral neuron fiber is the largest distributary of the lumbar plexus. This nerve is formed by the dorsal portion of the anterior branch of the L2-L4 spinal nerves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subgluteal approach to the sciatic nerve confers an increased motor blockade compared to its popliteal counterpart, and more extensive analgesia [14,15]. Due to its deeper location at this point, the proximal sciatic nerve may be more difficult to visualise.…”
Section: Subgluteal Approachmentioning
confidence: 99%